Licensed merchandise buying behavior of sports fans (Gaziantep Sport Store sample) - Huseyin Ozturk (Türk Spor ve Egzersiz Dergisi)
This study has been prepared to determine licensed team merchandise buying behavior of the fans that are coming to Gaziantep Sport Store to buy licensed merchandises. Research sample comprise of 439 people who are coming to Gaziantep Sport Store between the years of 2013-2015. Frequency, percentage, average, standard deviation have been used in evaluation; student t-test has been used for two independent groups having variables with normal distribution; ANOVA and LSD multiple comparison tests have been used for comparing more than two independent groups having variables with normal distribution. As a result of the study, the fans who are buying licensed merchandises in Gaziantep Sport Store, mostly watching the matches in the stadium; they prefer buying more licensed merchandises to identify with the team and support them; men prefer buying more licensed merchandise than women because of their loyalty and team identification while women prefer buying licensed merchandises more than men because of shopping enjoyment. When the style of watching Gaziantep Sport matches has been examined, it has been determined that there is a significantly difference between underlying dimensions of team identification, support, atmosphere, loyalty and shopping enjoyment.